Severe dengue encephalitis showcasing the “double doughnut sign” on MRI: A case report - Salhadin Mohammed; Aman Edao Bime; China Tolessa Sedi; Hussen Nuri Saliha; Surafel Tilahun Maru; Abdulfatah Workicho Mustafa (Radiology Case Reports)
Severe dengue can lead to fatal complications, including dengue encephalitis. We report a 14-year-old girl with severe dengue who presented with bilateral thalamic hemorrhagic infarction, indicated by distinct brain imaging findings (the so-called “double doughnut sign”), which is a rare presentation of a common infection. Positive dengue antigen and IgM tests were noted. The patient required critical care, including intubation and resuscitation, but was discharged improved and continues follow-up at our neurology clinic. This case highlights that dengue infection can be complicated by meningoencephalitis, and a high index of suspicion is needed to diagnose our patients promptly. Furthermore, imaging modalities such as MRI play a key role in diagnosing and managing patients with dengue encephalitis.